PHYSICAL DEVELOPMENT OF KHARKIV TEENAGERS IN 30 YEARS DYNAMIC - Danylenko, G.M.; Shvets, A.M.; Shvets, Y.M. (World of Medicine and Biology, 2016)
Since the PD is an indicator of health state, the purpose of the work was to study and compare the dynamics of PD of adolescents belonging to different generations. During the work an anthropometric survey of 15-18 years adolescents in 1985 and 2015 was carried out. As a result, the anthropometric research (weight and body length, chest circumference measurement) revealed that the main characteristics of the PD indicators in the studied contingent saved, but there is a negative trend – asthenization and disharmonization of PD (particularly by increasing of the number of adolescents with underweight). The results suggest a new spiral of acceleration and can be used to predict the similar indicators of future generations and to continue the search of causal factors in the formation of the younger generation’s health.